2018
DOI: 10.1128/iai.00244-18
|View full text |Cite
|
Sign up to set email alerts
|

The Protozoan Parasite Toxoplasma gondii Selectively Reprograms the Host Cell Translatome

Abstract: The intracellular parasite promotes infection by targeting multiple host cell processes; however, whether it modulates mRNA translation is currently unknown. Here, we show that infection of primary murine macrophages with type I or II strains causes a profound perturbation of the host cell translatome. Notably, translation of transcripts encoding proteins involved in metabolic activity and components of the translation machinery was activated upon infection. In contrast, the translational efficiency of mRNAs r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 109 publications
(103 reference statements)
1
37
0
Order By: Relevance
“…3D). Note that these compounds do not exert toxic effects on BMDM up to 24 h, as we previously described (45). Thus, these data provide evidence that L. donovani induces the expression of CXCL16 in macrophages via AKT/mTOR-dependent and TLR-independent mechanisms.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…3D). Note that these compounds do not exert toxic effects on BMDM up to 24 h, as we previously described (45). Thus, these data provide evidence that L. donovani induces the expression of CXCL16 in macrophages via AKT/mTOR-dependent and TLR-independent mechanisms.…”
Section: Resultssupporting
confidence: 82%
“…These results suggest that in addition to transcription, L. donovani might enhance the stability and/or the translation efficiency of Cxcl16 mRNA. Of note, we recently demonstrated that another protozoan parasite, Toxoplasma gondii, selectively regulates translation of immune-related transcripts in macrophages via the mTOR complex 1 (mTORC1), including chemokines (45). Therefore, sustained mTOR activity during L. donovani infection might be required to upregulate CXCL16 expression through both transcriptional and posttranscriptional mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The type I and III strains of T. gondii associate with mitochondria during infection and this association impacts cytokine responses (including increased pro-inflammatory IL-6 and CCL5, but also anti-inflammatory IL-10 production) during in vitro infection of BMDMs with T. gondii and ex vivo in peritoneal exudate cells (PECs) isolated from infected C57BL/6 mice. Therefore, the mitochondrial association and translation of mitochondrial transcripts via mTOR could be a possible route for the manipulation of the host immune response by T. gondii [177,178].…”
Section: Host Translationmentioning
confidence: 99%
“…In our assays, we corroborated that the stimulation of BMDCs with pLL and HF did not cause a significant decrease in cell viability ( Figure 1A), thus both antigens were used for the subsequent studies. Recognition of parasite-derived molecules induced not only the production of specific genes like cytokines, co-stimulatory molecules, or the up-regulation of MHC; but also promoted the transcription and translation of hundreds of genes, in order to control infection 50,51 . In this sense, mTOR appears to be part of the early sensing machinery, bridging the gap between PRR signaling and the cellular metabolism required to organize and trigger an effective immune response.…”
Section: Discussionmentioning
confidence: 99%